51.1k views
0 votes
Let f be the function defined by f(x)=x3+x2+x. Let g(x)=f−1(x), where g(3) = 1. What is the value of g'(3)?.

User Babernathy
by
4.6k points

1 Answer

5 votes

Quick review of the inverse function theorem:

By definition of inverse function,

f(f⁻¹(x)) = x

Differentiating both sides with respect to x using the chain rule gives

f'(f⁻¹(x)) • (f⁻¹)'(x) = 1

so that the derivative of the inverse is

(f⁻¹)'(x) = 1 / f'(f⁻¹(x))

Now if f(a) = b and a = f⁻¹(b), then the theorem says

(f⁻¹)'(b) = 1 / f'(a)

so that

g'(3) = 1 / f'(1)

We have

f(x) = x³ + x² + x ⇒ f'(x) = 3x² + 2x + 1 ⇒ f'(1) = 3 + 2 + 1 = 6

and so

g'(3) = 1/6

User Yekta
by
4.7k points